Analysis Of The Influence Of Financial Literacy And Financial Technology On Financial Satisfaction With Financial Management Behavior As Medition - Ameera, Najwa Saffa; Yuniningsih, Yuniningsih (UNIVERSITAS PAKUAN, 2025)
inancial satisfaction is one of the goals that individuals want to achieve to obtain well-being in life, as a result of decisions in financial behavior. This is influenced by individual behavior in managing finances, which is also shaped by an individual's financial literacy and their use of financial technology. This research aims to investigate the influence of financial literacy and financial technology on financial satisfaction, with financial behavior acting as an intervening variable, in Management students of UPN